2021
DOI: 10.2196/26987
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Psychological Mechanisms of an App-Based Digital Therapeutic for Generalized Anxiety Disorder: Randomized Controlled Trial

Abstract: Background Current treatments for generalized anxiety disorder (GAD) often yield suboptimal outcomes, partly because of insufficient targeting of underlying psychological mechanisms (eg, avoidance reinforcement learning). Mindfulness training (MT) has shown efficacy for anxiety; yet, widespread adoption has been limited, partly because of the difficulty in scaling in-person–based delivery. Digital therapeutics are emerging as potentially viable treatments; however, very few have been empirically va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 78 publications
(95 reference statements)
0
38
1
1
Order By: Relevance
“…This study is a secondary data analysis of a previously described stage 1 parallel-group RCT [ 32 ]. As this secondary analysis is interested in system use data and their association with study outcomes, data were taken from the intervention arm only, and study procedures relevant to analyzing the intervention group are summarized in the following sections [ 32 ]. Roy et al [ 32 ] provide detailed information on the study design, procedures, and the results of the randomized trial.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is a secondary data analysis of a previously described stage 1 parallel-group RCT [ 32 ]. As this secondary analysis is interested in system use data and their association with study outcomes, data were taken from the intervention arm only, and study procedures relevant to analyzing the intervention group are summarized in the following sections [ 32 ]. Roy et al [ 32 ] provide detailed information on the study design, procedures, and the results of the randomized trial.…”
Section: Methodsmentioning
confidence: 99%
“…The data used for these analyses were from the baseline and 2-month time points for the intervention group only [32]. The inclusion criteria were as follows: (1) score ≥10 on the Generalized Anxiety Disorder 7-item scale (GAD-7), (2) owning a smartphone, (3) willingness to receive check-in calls, and (4) aged ≥18 years [32]. Participants were excluded from the study if they reported (1) dose changes of any psychoactive medication in the previous 2 months; (2) needed use of benzodiazepines and hypnotic sleep aids; (3) a history or current diagnosis of bipolar, schizophrenia or schizoaffective, or another psychotic disorder; (4) a significant medical condition that would affect the ability to complete study tasks; (5) cohabitation with someone already enrolled in the study; and (6) having a previous history of using other related apps, specifically Eat Right Now or Craving to Quit, which use similar reinforcement processes to UA [33][34][35].…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging data suggest that mindfulness training apps may be effective across a range of psychiatric illnesses, including generalized anxiety disorder and nicotine use disorder. And, at least in nicotine use disorder, the mechanism seems to be exactly what we already knew: changes in functioning of the DMN (7,8).…”
mentioning
confidence: 87%